The municipality as a source of information? - Vavrek, Roman; Kravčáková Vozárová, Ivana; Cehlárová, Martina; Ondrijová, Ivana (Journal of Economic Development, Environment and People, 2014)
The municipality as an entity of the local government and disposes defined rights and obligations, which are governed by the special regulations. In accordance with Act no. 211/2000 Coll. on free access to information, the municipality is mandatory publish and make available information that this Act also more specify. This paper focuses on availability of information from websites or other available sources. The basic set was represented by 91 municipalities of Prešov district, in which were surveyed a total of 75 data (6 identification and 69 financial). Within the implemented questioning, we can conclude especially the availability of identification data, for which there are multiple sources (eg. number of inhabitants). Overall, however, the municipalities did not provide the requested information, when up to 27 municipalities did not provide more than 5 data (including 3 identification). One of the outcomes is also a proving of small correlation between the volume of data obtained from the municipality and the number of its inhabitants, respectively the distance from the district town.